Locally Advanced Pancreatic Cancer: Is It Possible Pancreatic Resection? A Case Report - Di Marco, Mariacristina; Zingaretti, Caterina Costanza; Ricci, Claudio; Vecchiarelli, Silvia; Taffurelli, Giovanni; Macchini, Marina; D’Ambra, Marielda; Buscemi, Salvatore; Monari, Francesco; Casadei, Riccardo; et al. (JOP. Journal of the Pancreas, 2013)
Context Patients with locally advanced pancreatic cancer are usually treated with chemoradiotherapy and rarely they became resectable. Herein, we present the case of a patient with locally advanced pancreatic cancer. Case report A 56-year-old man was observed in October 2011 because of high blood levels of CA 19.9 (>230 U/mL) and the presence of a pancreatic mass of the uncinate process (diameter 3.8x3.5 cm) revealed by US and CT scan. An US-guided biopsy allowed the diagnosis of well differentiated pancreatic adenocarcinoma, biliopancreatic type. CT scan showed a vascular involvement of both superior mesenteric vein and artery. The disease was defined as locally advanced unresectable pancreatic cancer. The patient started chemotherapy with gemcitabine and oxaliplatin. Five months later, CT scan re-evaluation of the disease showed a stable disease. Thus, a protocol of radio-chemotherapy was suggested. Eight months later from diagnosis, the mass was still unresectable. Other eight cycles of gemcitabine and oxaliplatin were performed. In February 2013 a further CT scan evaluation demonstrated a smaller lesion (3.5x2.2 cm) and also the vascular involvement was decreased, still without a normal fat plane between the tumor and the vessels. Another cycle of gemcitabine and oxaliplatin was completed. At the end of May 2013, the 18FDG-PET was negative; CT scan demonstrated a further decreased of the mass (maximum diameter: 2.5 cm) while the mesenteric vessels involvement still remained. Moreover, the genomic characteristics of the patient DNA were different from other the pancreatic cancer. Because of the long-term survival of the young patient, the partial regression of the disease and the genomic characteristics of the tumor, a surgical approach was indicated. The patient underwent to a total pancreatectomy with splenectomy plus segmental resection of portal mesenteric trunk. Pathological diagnosis confirmed a well-differentiated ductal pancreatic carcinoma, biliopancreatic type (T4), with R0 resection. Conclusion Our case suggests that there are locally advanced pancreatic cancers in which chemoradiotherapy can allow surgical pancreatic resection probably because they have particular genomic characteristics.